Young male namings in Russian and Chinese in the diachronic aspect - Wenjuan, Wang (Journal of the Belarusian State University. Philology, 2019)
The article deals with the retrospective analysis of young mail namings in two languages, Russian and Chinese. The author comes to the conclusion that there exist some similarities in the semantic development of the corresponding lexemes in these two languages. Despite the fact that both languages and cultures are remoted from each other, semantic changes may have similar reasons caused by the generality of human concepts of the described age period.
Keywords: naming; young mail namings; word semantics; development of word semantics; comparative analysis; multisystem languages